2019
DOI: 10.1002/acn3.796
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic enhancement of sleep slow oscillations in mild cognitive impairment

Abstract: Objective Slow‐wave activity (SWA) during sleep is reduced in people with amnestic mild cognitive impairment (aMCI) and is related to sleep‐dependent memory consolidation. Acoustic stimulation of slow oscillations has proven effective in enhancing SWA and memory in younger and older adults. In this study we aimed to determine whether acoustic stimulation during sleep boosts SWA and improves memory performance in people with aMCI. Methods Nine adults with aMCI (72 ± 8.7 years) completed one night of acoustic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 50 publications
3
87
0
Order By: Relevance
“…Hence, optogenetic manipulation of both SO and sleep spindle events directly impacts long-term memory retention, supporting their causal role in sleep-dependent memory consolidation. This model is further supported by studies that mechanistically enhance slow waves, sleep spindles, and slow wave-sleep spindle coupling through external electrical and auditory stimulation methods in humans, resulting in improved procedural and episodic memory, even in older adults and patients with MCI (Marshall et al, 2004(Marshall et al, , 2006Westerberg et al, 2015;Lustenberger et al, 2016;Ladenbauer et al, 2017;Papalambros et al, 2017Papalambros et al, , 2019.…”
Section: Direct Effectsmentioning
confidence: 79%
See 1 more Smart Citation
“…Hence, optogenetic manipulation of both SO and sleep spindle events directly impacts long-term memory retention, supporting their causal role in sleep-dependent memory consolidation. This model is further supported by studies that mechanistically enhance slow waves, sleep spindles, and slow wave-sleep spindle coupling through external electrical and auditory stimulation methods in humans, resulting in improved procedural and episodic memory, even in older adults and patients with MCI (Marshall et al, 2004(Marshall et al, , 2006Westerberg et al, 2015;Lustenberger et al, 2016;Ladenbauer et al, 2017;Papalambros et al, 2017Papalambros et al, , 2019.…”
Section: Direct Effectsmentioning
confidence: 79%
“…While there are some data that suggest that treating sleep disorders may impact AD biomarkers ( Osorio et al, 2015 ; Liguori et al, 2017a , b ), large scale studies are lacking. Further, while a few reports show that enhancing local sleep in older adults and patients with MCI will improve overnight memory consolidation ( Ladenbauer et al, 2017 ; Papalambros et al, 2019 ), the efficacy of this type of intervention, even for more than one night, is unknown. As important is an examination of the impact of AD disease stage on the efficacy of sleep interventions to impact AD pathophysiology and related cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairment in aging is also indicated to be related to suppressed slow waves (41,42). A trial demonstrated that enhancing slow wave activity conducted by acoustic stimulation was associated with improved morning word recall in individuals with aMCI (43). Accumulation of amyloid-β and tau aggregates, two histopathological markers of AD in the brain, are demonstrated to correlate with decreased SWS (44).…”
Section: Discussion Main Findings and Discussionmentioning
confidence: 99%
“…There has to date been only one study of acoustic augmentation of SWS in a neurodegenerative cohort [227]. Conducted in 2019, this nocturnal pilot study in nine patients with amnestic mild cognitive impairment demonstrated highly variable increases in slow-wave activity (1-30%), but promisingly, improvement in declarative memory was demonstrated in five of nine participants, and the degree of improvement correlated with that of slow-wave activity augmentation.…”
Section: Acoustic Stimulationmentioning
confidence: 99%